(untitled) (KULT_online, 2015)
Literary scholar Hans Ulrich Gumbrecht has compiled 23 essays, which cover the entire range of Kittler’s unorthodox explorations of Western media networks and discourses. This edited volume makes some of Kittler’s essays available for the first time for the English-speaking public; furthermore, the editor convincingly explicates Martin Heidegger’s conception of modern technology as common ground of Kittler’s entire oeuvre.